2011
DOI: 10.1093/schbul/sbr049
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Gender Influence on Cortical and Subcortical Gray Matter Development in Childhood-Onset Schizophrenia

Abstract: Sex appears to play a similar role in cortical and subcortical GM development in COS as it does in normally developing children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
1
9
1
Order By: Relevance
“…This is consistent with previous findings in our group, which indicated no gender differences in cortical thickness, subcortical volume development, 34,35 or cortical gray matter development 36 . These findings also corroborate findings of AOS studies 27 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with previous findings in our group, which indicated no gender differences in cortical thickness, subcortical volume development, 34,35 or cortical gray matter development 36 . These findings also corroborate findings of AOS studies 27 .…”
Section: Discussionsupporting
confidence: 94%
“…A small longitudinal study (n=21) found males with early-onset schizophrenia (EOS) to have more frontal gray matter loss compared to controls than females with EOS, although that study was underpowered to detect change in women due to small sample size (23.81% female n=5) 33 . Earlier studies in our group have found no gender differences in cortical thickness and subcortical volume development 34,35 or development of total cortical gray matter 36 in patients with COS. Nevertheless, while changes in cortical brain volume are among the most consistently reported abnormalities in both AOS and COS, a thorough and systematic evaluation of potential gender differences remains lacking 37,38 .…”
Section: Introductioncontrasting
confidence: 60%
“…In a meta-analysis of longitudinal MRI studies in children and adolescents with early onset psychosis, the proportion of males in each study was not found to significantly impact regional brain volume effect sizes [140]. Likewise, a longitudinal sample of youth with childhood-onset schizophrenia found no sex differences for either cortical thickness or subcortical volumes [160]. Moving forward, it will be important for future research to determine when sex differences in regional volumes emerge during development in youth at risk for psychosis symptoms.…”
Section: Psychosismentioning
confidence: 93%
“…It has also been established that COS probands do not differ from healthy controls with regards to sex differences in cortical thickness (Weisinger et al, 2013), or with regards to cross-sectional or longitudinal developmental changes in asymmetry (Bakalar et al, 2009). Cortical thickness deficits in COS probands are also largely uninfluenced by clozapine versus olanzapine intake, aside from a small area of the right prefrontal cortex (Mattai et al, 2010).…”
Section: 2 Structural Neuroimagingmentioning
confidence: 99%